Ruthenium (II) complexes with N, O-chelating proline and threonine ligands cause selective cytotoxicity by the induction of genomic instability, cell cycle arrest and apoptosis in breast and prostate tumor cells. (February 2020) - de Sousa, Israel Higino; Campos, Vanessa Niely Soares; Vale, André Alvares Marques; Maciel-Silva, Vera Lucia; Leite, Celisnolia Moraes; Lopes, Alberto Jorge Oliveira; Mourão, Penina Sousa; das Chagas Alves Lima, Francisco; Batista, Alzir Azevedo; de Azevedo dos Santos, Ana Paula Silva; Almeida, Marcio Aurélio Pinheiro; Pereira, Silma Regina Ferreira
Abstract: Ruthenium complexes are being considered as novel chemotherapeutic alternatives for cancer treatment. In our study, we assessed the antitumoral activities of novel ruthenium complexes coupled to the amino acids proline (RuPro) and threonine (RuThr) in prostate tumor cell lines (DU145) and breast (MCF7), and normal cell lines of the lung fibroblast (GM07492A). Our results revealed that the EC50 of the complexes for DU145 and MCF7 was two times lower than that GM07492A. Moreover, RuPro and RuThr were not able to induce significant genomic instability, cell cycle arrest or cell death in GM07492A, but could induce DNA damage, arrest in G2/M and apoptosis in DU145 and MCF7. Furthermore, BAX, TP53 and ATM were found to be upregulated in DU145 and MCF7 treated with RuPro and RuThr, in which, a higher ASCT2 gene expression was also observed. Using molecular docking, RuPro and RuThr interact with ASCT2, suggesting that this transporter might have a pivotal role in the execution of their activities. Hence, our results with RuPro and RuThr are capable of selectively inducing genetic damage, cell cycle arrest and apoptosis in DU145 and MCF7. We suggest that the selective action of the RuPro and RuThr complexes is related to the higher expression of ASCT2 in the tumor cells. Graphical abstract: Unlabelled Image Highlights: Ruthenium (II) complexes with ligands N, O-chelating proline or threonine are cytotoxic to tumor cells. EC50 values in the range of 30 to 40 μM were determined in tumor cells. The complexes also exhibit a genotoxic effect, cell cycle arrest and induce cell death by apoptosis.